Revitalization of Self-Identity of the Penelando Islamic Indigenous Community Amidst Global Cultural Change in Sasak Community - Hidayat, Asep Achmad; Rohandy, Fajar; Ilhami, Hablun (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2024)
This study aims to examine the revitalization of self-identity within the Penelando Islamic indigenous community of the Sasak people in response to global cultural change. As globalization intensifies, indigenous communities face increasing challenges in preserving their cultural and religious identity while adapting to external influences. The Penelando community represents a unique case of cultural resilience, where tradition and modernity intersect. Using a qualitative descriptive approach with a sociological perspective, this research collects data through in-depth interviews with community members and stakeholders, as well as a literature review of relevant books and journal articles. The findings indicate that the Penelando Islamic indigenous community embodies an acculturative cultural-religious identity, reflected in their adaptive strategies, such as integrating modern agricultural practices with traditional belief systems. Traditional stakeholders play a critical role in maintaining communal identity by negotiating cultural continuity and change. Their accommodative stance allows them to selectively adopt global elements while preserving core values. This study contributes to the discourse on indigenous identity preservation by highlighting the dynamic interplay between local traditions and global influences. Further research is needed to explore similar adaptive strategies among other indigenous communities facing globalization, particularly in regions experiencing rapid socio-cultural transformation.